Eighteen years of Antillean manatee Trichechus manatus manatus releases in Brazil: lessons learnt. Issue 2 (19th August 2014) - Normande, Iran Campello; Luna, Fabia De Oliveira; Malhado, Ana Cláudia Mendes; Borges, João Carlos Gomes; Viana Junior, Pitágoras Carlos; Attademo, Fernanda Löffer Niemeyer; Ladle, Richard J.
Abstract: The Antillean manatee Trichechus manatus manatus was once widespread from the south-eastern coast of Brazil to Central America and the Caribbean. In Brazil habitat destruction and overhunting severely reduced and fragmented the wild population, restricting extant subpopulations to the north and north-east coast. In response to these threats an ambitious government-led programme was initiated in 1994, with the aim of rehabilitating orphaned manatee calves and releasing them into the southernmost subpopulation. The programme is unique within Brazil, and has invested unprecedented resources in post-release monitoring. So far 30 manatees have been released at three sites, with a high rate of success (> 75%). Time in captivity appears to be a key variable determining post-release success: too long or too short a time in captivity decreasing the probability of survival. We describe the main features of this long-term programme and identify six key lessons learnt: (1) close monitoring, health assessments and rescues can significantly increase the success of releases, (2) combining different monitoring techniques results in high-quality data and reduces tracking costs, (3) long-term studies are needed to effectively evaluate the results, (4) releasing manatees at c. 5 years of age can increase chances of success, (5) soft-release is important to aid acclimatization, and (6) the programme has been effective in raising awareness among the general public, supporting education and fund-raising.